The Association Between Religious Belief and Treatment Adherence Among Those with Mental Illnesses - Kavak Budak, Funda (Journal of religion and health, 2021)
This study was conducted to determine the association between religious belief and treatment adherence among those with mental illness. The sample size of this cross-sectional study was determined to be 255 patients diagnosed with mental illness via power analysis. A descriptive characteristics form prepared by the researcher, the Systems of Belief Inventory, and the Morisky Medication Adherence Scale were used to collect data. Patients were listed and chosen by using a simple random sampling method. This study found no significant correlation between religious belief and treatment adherence (p > .05). It was determined that treatment adherence was moderate in patients with high religious beliefs and that treatment adherence was low in patients with low religious beliefs. Religious belief was not a factor influencing treatment adherence among those with mental illness.